ANALISIS MAQASHID SYARI’AH TERHADAP RELEVANSI BESARAN IWAD DALAM SIGHAT TAKLIK TALAK - Erma, Erma Sauva Asvia (Institut Agama Islam Darul Ulum Kandangan, 2023)
This research departs from the Decree of the Minister of Religion No. 411 of 2000 concerning Determination of the Amount of Iwad Money in the Sighat Taklik Divorce Series for Muslims, namely Rp. 10,000.00 which has not been changed for 20 years, even though the laws in Indonesia and other regulations have changed or equalized the amount of money both in terms of fines and so on. This study aims to determine whether the Decree of the Minister of Religion No. 411 of 2000 concerning Determination of the Amount of Iwad Money in the Sighat Taklik Divorce Series for Muslims, namely Rp. 10,000.00 is still relevant to the Indonesian economy at this time. This research is a library research (Library Research). The subject is a number of literature related to the problems studied such as books, documents, articles, research results and laws and regulations that are relevant in analyzing the problems studied. As for the object of research in this study is the relevance of the amount of iwad in sighat taklik divorce in the review of maqasid shari'ah. This research resulted in the finding that the Decree of the Minister of Religion No. 411 of 2000 concerning Determining the Amount of Iwad Money in the Sighat Taklik Divorce Series for Muslims is Rp. 10,000.00 which was analyzed from the review of maqashid syari'ah which is in accordance with the intent of maqashid syari'ah and is included in the maslahah section, namely hifz nafs. It's just that there needs to be changes and adjustments regarding the amount of iwad money because it is no longer relevant to the current economic inflation.